The Role of JAKIM and Islamic Education Curriculum in Shaping the Discourse of Wasatiyyah in Malaysian Secondary Schools - Daud, Mohd Razali bin; Ismail, Ahmad Fauzi bin (Bestari, 2025)
This article explores the role of Malaysia’s Department of Islamic Development (JAKIM) and the national Islamic education curriculum in promoting the discourse of wasatiyyah, or Islamic moderation, among secondary school students. Employing content analysis and semi-structured interviews with curriculum developers and teachers, the study investigates how concepts of balance, tolerance, and ethical coexistence are embedded within teaching materials and classroom practices. Findings show that JAKIM’s policy direction strongly influences curricular emphasis on moderation, countering extremism, and strengthening national unity. However, variations in teacher interpretation and pedagogical approaches affect the consistency of implementation. The paper argues that achieving meaningful internalization of wasatiyyah requires enhancing teacher training, integrating real-life case studies, and fostering dialogical learning environments. This research contributes to broader discussions on state-led religious discourse and curriculum-based strategies for promoting social harmony in multicultural societies.